Pendampingan TPACK (Technological Pedagogic and Content Knowledge) di SMA Negeri 1 Pengasih - Nuryadi Nuryadi; Nafida Hetty Marhaeni; Anief Fauzan Rozi (I-Com: Indonesian Community Journal, 2023)
The TPACK (Technological Pedagogic Content Learning) approach is an approach that contains four types of mandatory competencies for professional teachers. This is because the mastery of the interaction between pedagogy and content to implement strategies that help students understand the material needs to be mastered by professional teachers. Therefore, the purpose of this service is to provide TPACK assistance in the form of developing technology-based learning content at Pengasih 1 Public High School. The method of implementing community service is carried out online through training, workshops and mentoring. The results of the service show that teachers at SMA Negeri 1 Pengasih are able to create learning content that is integrated with technology through the help of a liveworksheet website. In addition, teachers' knowledge of the integration of pedagogic, content, and technology in learning is increasing because of this training. Therefore, this service has been able to achieve the target set by the servant, namely making teachers at SMA Negeri 1 Pengasih able to implement TPACK in learning.